After Norway's terrorist attacks : time to refocus priorities - Tuty Raihanah Mostarom (2012)
The chain of events after the recent terrorist attacks in Oslo tests our ability to tackle the issue of terrorism a decade after September 11. Have the authorities truly learnt anything in dealing with the ideologies and motivations behind acts of terror?